Provider perceptions of challenges to identifying women Veterans with hazardous substance use - Karleen F. Giannitrapani; Jesse R. Holliday; Andrew W. Dawson; Alexis K. Huynh; Alison B. Hamilton; Christine Timko; Katherine J. Hoggatt (BMC, 2022)
Abstract Background Approximately one-third of women Veterans Health Administration (VHA) users have substance use disorders (SUD). Early identification of hazardous substance use in this population is critical for the prevention and treatment of SUD. We aimed to understand challenges to identifying women Veterans with hazardous substance use to improve future referral, evaluation, and treatment efforts. Methods Design: We conducted a secondary analysis of semi-structured interviews conducted with VHA interdisciplinary women's SUD providers at VA Greater Los Angeles Healthcare System. Participants: Using purposive and snowball sampling we interviewed 17 VHA providers from psychology, social work, women's health, primary care, and psychiatry. Approach: Our analytic approach was content analysis of provider perceptions of identifying hazardous substance use in women Veterans. Results Providers noted limitations across an array of existing identification methodologies employed to identify women with hazardous substance use and believed these limitations were abated through trusting provider-patient communication. Providers emphasized the need to have a process in place to respond to hazardous use when identified. Provider level factors, including provider bias, and patient level factors such as how they self-identify, may impact identification of women Veterans with hazardous substance use. Tailoring language to be sensitive to patient identity may help with identification in women Veterans with hazardous substance use or SUD who are not getting care in VHA but are eligible as well as those who are not eligible for care in VHA. Conclusions To overcome limitations of existing screening tools and processes of identifying and referring women Veterans with hazardous substance use to appropriate care, future efforts should focus on minimizing provider bias, building trust in patient-provider relationships, and accommodating patient identities.